2015
DOI: 10.1097/gox.0000000000000447
|View full text |Cite
|
Sign up to set email alerts
|

Haptics-assisted Virtual Planning of Bone, Soft Tissue, and Vessels in Fibula Osteocutaneous Free Flaps

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 28 publications
0
33
0
1
Order By: Relevance
“…This demonstrated that it is possible to integrate clinical knowledge of experienced surgeons in such a software tool and motivates us to integrate more clinical constraints, e.g. the individual supply of blood vessels, into a further evolved version of the software. Thus, we demonstrated the potential use of artificial intelligence in the surgical setting.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This demonstrated that it is possible to integrate clinical knowledge of experienced surgeons in such a software tool and motivates us to integrate more clinical constraints, e.g. the individual supply of blood vessels, into a further evolved version of the software. Thus, we demonstrated the potential use of artificial intelligence in the surgical setting.…”
Section: Discussionmentioning
confidence: 97%
“…The fundamental difference of the present approach from published works with similar intentions is that the three‐dimensional bone surface geometries are simplified to curves that follow certain anatomical features. The advantage of using these curves to define the relevant contour of the target shape is that it reduces the overwhelmingly complex task of mandibular reconstruction to a manageable procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Hapticsassisted virtual planning, which allows planning of soft tissue and vessels in addition to bone for free fibula flaps has addressed some of these limitations, but additional developments are needed. 28 Despite these limitations, CASS can improve efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…These recent studies address major issues in clinical outcomes and patient satisfaction. [34] developed a haptics-assisted planning system that incorporates bone resection, fibula design, recipient vessel selection, pedicle and perforator location selection, and skin paddle configuration. [35] demonstrated the cost advantages of preoperative planning.…”
Section: Related Workmentioning
confidence: 99%